Literacy is an Important Factor in Professional Training of Modern Specialist - Tsyhanenko, V.; Ochkurova, N.; Serhiieva, A. (MC&FPGA, 2020)
The abstracts of the report draw attention to such a factor as language literacy, which is extremely important in any communication in the professional field. The problems that arise when using words-terms of foreign origin, verb nouns, adjectives and verbs are considered. Attention is drawn to the difficulties of translating professional terms, especially from the Russian language.
Keywords: borrowing; foreign origin; verb nouns; terminology; terms; suffixes